Local fiscal consolidation in Korea : debt and liabilities of public enterprises - Kim, Hyun-A (The Korea Institute of Public Finance SeoulKR, 2013)
Aims to examine and discuss relevant issues regarding the debt status of local governments and the liability held by local public enterprises, with the eventual aim to characterise the nature of local government debt.